1978
DOI: 10.1128/aem.35.6.995-1002.1978
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ribonucleic acid coliphages in south and east Asia

Abstract: We investigated the distribution of ribonucleic acid (RNA) coliphages in the Philippines, Singapore, Indonesia, India, and Thailand by collecting sewage samples from domestic drainage in November 1976. Of the 221 samples collected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 11 publications
(13 reference statements)
5
36
1
Order By: Relevance
“…According to published literature, F-RNA phage genotypes II and III have been detected only in human faeces and genotypes I and IV in animal faeces (Hsu et al 1995;Beekwilder et al 1996;Hsu et al 1997;Uys 1999;Grabow 2001). This is in agreement with reports on the incidence of serotypes in human and animal faeces (Furuse et al 1978;Furuse et al 1981;Osawa et al 1981;Havelaar et al 1986). The only exception to this rule on record is the detection of serotype II bacteriophages in pig faeces and the detection of serotype IV in human faeces (Havelaar et al 1990).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…According to published literature, F-RNA phage genotypes II and III have been detected only in human faeces and genotypes I and IV in animal faeces (Hsu et al 1995;Beekwilder et al 1996;Hsu et al 1997;Uys 1999;Grabow 2001). This is in agreement with reports on the incidence of serotypes in human and animal faeces (Furuse et al 1978;Furuse et al 1981;Osawa et al 1981;Havelaar et al 1986). The only exception to this rule on record is the detection of serotype II bacteriophages in pig faeces and the detection of serotype IV in human faeces (Havelaar et al 1990).…”
Section: Discussionsupporting
confidence: 82%
“…Consequently, the composition of genotypes in raw sewage and, particularly, treated wastewaters as well as environmental water sources may be subject to age, treatment and exposure to unfavourable conditions. Furuse et al (1978) found that subgroup II F-RNA phages seemed to predominate in cold regions and subgroup III phages in warm climates. They concluded that the incidence of genotypes may be affected by geographical factors.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this study, a higher prevalence of FRNA G2 (detection frequency ¼ 52.3%) was found compared to FRNA G3 (detection frequency ¼ 5%). This finding contradicts an earlier study which reported that FRNA G2 seems to be more prominent in cold regions, while FRNA G3 dominated in warm regions (Furuse et al, 1978). One of the possible reasons could be the higher persistence of FRNA G2 compared to FRNA G3 in natural environments (Schaper et al, 2002a).…”
Section: Microbial Indicatorscontrasting
confidence: 88%